Application of the Educational Media Ludo Monopoli (LUPI) to Improve Teaching Skills of Elementary School Teachers in Dili - Raharjo, Tri Joko; Harianingsih, Harianingsih; Bunyamin, Bunyamin; Hidayati, Wiwik; Ginanjar, Bagus; Yuliyani, Atik; Akhilia, Tudrika (Universitas Negeri Semarang, 2025)
The use of innovative learning media has been considered a strategic effort to enhance teaching effectiveness at the elementary school level, especially for conceptual subjects such as the human digestive system. In Dili, Timor-Leste, limited access to contextual learning media and the lack of pedagogical training for teachers have been identified as real challenges in the learning process. This community service activity was designed to improve the skills of elementary school teachers in Dili in utilizing the LUPI (Ludo Monopoli) learning media for the topic of the digestive system. LUPI is an interactive educational media based on a board game, which was developed to facilitate student understanding in an active and enjoyable manner. The implementation method was composed of training, direct practice, reflective discussion, and skills evaluation. The activity was conducted for two days at Universidade Católica Timorense (UCT) São João Paulo II and was participated in by 10 local elementary school teachers. Significant improvements were shown in teachers' understanding of digestive system concepts and in their ability to design and implement the LUPI media in teaching. Moreover, it was stated by the teachers that the use of LUPI increased student engagement, clarified concepts, and encouraged interest in learning. It is recommended that follow-up training based on thematic curriculum and replication of similar media for other topics be provided. The collaboration between educational institutions from Indonesia and Timor-Leste has been proven effective in addressing cross-national pedagogical challenges through an approach rooted in local wisdom and educational games.